Rancang Bangun Sistem Control Otomatisasi dengan mengintegrasikan PLC - Lasro P. Sihite; Dharmanto; Lala (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2026)
The cyanide mixing process in the PT CBA reagent area was previously carried out manually, which was not only inefficient, but also required a long time for one mixing process and also increased occupational safety risks due to exposure to hazardous chemicals. This research aimed to design and build an automation system using an Allen-Bradley PLC and a Citect SCADA to replace this manual process. The system was developed using an ultrasonic sensor to measure liquid levels, with ladder diagram control logic on the PLC to regulate water filling, agitator activation, and valve operation automatically. Integration between the PLC and SCADA was carried out through the conversion of the DH+ protocol to Ethernet TCP/IP to enable real-time process monitoring and control from the HMI interface. Testing was carried out through program logic verification and interviews with 6 operators.